The Value of Liberal Feminism in “Sì” Giorgio Armani Perfume Line Advertisement - Tjiang Jennifer Chandra; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study aims to find out how verbal communication and visual signs in the "Sì" Giorgio Armani Perfume Line Advertisement reflect the value of liberal feminism. In conducting the study, I used Danesi's theory of Signs in semiotics (2004). This study was done using a qualitative approach in which I transcribed both the song lyrics and the narration that appeared in the video. I also captured the scene of the video to analyze the visual sign aspects. For this study, I analyzed the visual sign through the actress's body language, facial expression, and the color that often appeared in the video advertisement. The data finds that the "Sì" by Giorgio Armani perfume line advertisement uses the concept of liberal feminism to appeal to a modern and empowered audience of women. By incorporating messages of individual choice, empowerment, and self-affirmation, the advertisement positions itself as a brand that supports and celebrates the values of liberal feminism.